Impact of my strategy (Think - Pair - Share) And (probing questions) in the collection and retention of science for students Fifth grade (Journal of the College of Basic Education, 2022)
The current research aims to identify the impact of the strategies (Think - Pair - Share) and (Probing Questions) on the collection and retention of science subject among the fifth grade students. According to the strategy (Think - Pair - Share) and (23) students in the second experimental group studying according to the (probing questions) strategy and (23) students in the control group studying according to the traditional method, the researcher was rewarded in the three research groups in the variables of age time period calculated in months, intelligence, academic achievement of parents, and academic achievement in science for the fourth grade of primary school) The researcher prepared a test